Comparative study of the sputtering yield and photovoltaic efficiency in photovoltaic materials - Souad Merabet (Revue des Énergies Renouvelables, 2023)
The comparison of the results obtained from argon ions and those obtained from neon ions in various photovoltaic materials in this work led to the identification of factors influencing the ionic sputtering deposition method as well as the effect of the used ion beam type. The SRIM simulation software was used in the study. According to the results, the sputtering yield increases proportionally with the angle and energy of incidence up to a certain point, then decreases. Furthermore, the value disparity confirmed the close relationship between the spraying process and the material structure. The same findings were made when the electronic and nuclear stopping powers were calculated. Solar cells were then simulated using the materials under consideration.